PERSEPSI PEMANFAATAN PERPUSTAKAAN TERHADAP MOTIVASI PENULISAN SKRIPSI MAHASISWA PERPUSTAKAAN DAN ILMU INFORMASI UNIVERSITAS NEGERI PADANG - Ashidiqi, Muhammad Ibra; Nabila, Jeihan (Scinary, 2023)
"Perceptions of Library Use on Thesis Writing Motivation of Library and Information Science Students at Padang State University." Thesis. Library and Information Science Study Program, Department of Information and Library Science, Faculty of Languages and Arts, Padang State University. This research was motivated by the lack of motivation to use the library in looking for reading materials for thesis writing within the Padang State University environment. Most students look for references more from the internet such as Google Scholar and the UNP digital library than from the library, resulting in fewer library visits at the Faculty of Languages and Arts. This research aims to describe the perception of library use on the motivation for writing a thesis for Library and Information Science students at Padang State University. This research is quantitative research. The population in this study was 97 people and the sample for this study was 50 Library and Information Science students at Padang State University using a simple random sampling technique using the Slovin formula. The analysis of this research uses the T test. The results of this research show (1) Perception of library utilization of Padang State University Library and Information Science students in the Good category (2) Padang State University Library and Information Science student's thesis writing motivation in the Good category (3) Library utilization has a significant effect on student thesis writing motivation Padang State University library and information science.